SCHOOL LEARNING ACTION CELL AS A REMEDY TO OUT-OF-FIELD TEACHING: A CASE IN ONE RURAL SCHOOL IN SOUTHERN PHILIPPINES - Jayson Troy Ferro Bajar; Mary Ann Ferro Bajar; Elizabeth P Alarcon (Universitas Ahmad Dahlan, 2021)
out-of-field teaching continues to be a persisting problem in the Philippine educational system similarly evident in the rural school where this study was conducted. As an intervention, the researchers organized a professional learning community in the form of a school learning action cell (SLAC) to provide assistance to the teachers. They were then interviewed to determine the perceived effects of the intervention. Results of the study revealed that SLAC sessions contribute to the general well-being of the teachers in their view of the profession as it reduced their tasks and promoted workplace collaboration. On the other hand, it also impacted their pedagogy, which was found to have contributed to their instructional mastery and teacher efficacy. The researchers, however, caution that, though the intervention was found to be successful, it should be taken in its suggestive nature when out-of-field teaching is unavoidable. When feasible, the idyllic educational landscape should assign teachers according to their respective specialized fields.